In-situ testing of a low intervention NSM seismic strengthening technique for historic URM buildings. (16th August 2011) - Dizhur, Dmytro; Derakhshan, Hossein; Griffith, Michael; Ingham, Jason
Due to the poor seismic performance of unreinforced masonry (URM) buildings there is a need for a cost effective minimally-invasive seismic retrofit technique. Most research considering out-of-plane seismic retrofit of URM walls has been conducted using laboratory-based studies with well defined but artificial boundary conditions, using constituent construction materials that attempt to simulate the material properties of masonry found in historic URM buildings. Thus, in-situ testing of retrofitted URM walls is required to provide data with which to validate the accuracy of laboratory-based studies. An experimental campaign was executed to investigate the performance of a near-surface mounted (NSM) carbon fibre reinforced polymer (CFRP) seismic retrofit solution. This campaign involved testing of five masonry walls loaded out-of-plane in four different buildings located in New Zealand. Testing confirmed that the CFRP retrofit technique is an excellent minimally-invasive and cost effective option for seismic strengthening of URM buildings. Details of the history of the buildings, and the methods used to undertake the field tests are reported, and experimental results are presented.